Addicted in Afghanistan - Taiman, Jawed (United Kingdom : Katalyst Productions, 2009)
One million Afghans are estimated to be addicted to drugs, especially heroin. Alarmingly, 40% of these are women and children. "Addicted in Afghanistan" is an intimate observational documentary that explores the reality behind the headlines as seen through the eyes of Jabar and Zahir, two 15 year old drug addicts living in Kabul. Filmed over a year, the film presents the day to day struggles of a new generation of children addicted to heroin, trying to find their way in the new Afghanistan.
Verzio Film Festival Submission
Duration: 01:18:00
Verzio Film Festival Submission
Keywords: Documentary films